Pengembangan Produk Perbankan Syariah untuk Menjangkau Segmen Pasar yang Lebih Luas - Rantisi, Muhammad Agil; Winario, Mohd (Multidisciplinary Journal of Religion and Social Sciences, 2024)
The Islamic banking industry has become a key pillar in the global financial system, offering an alternative that is in line with Islamic principles and attracting interest from an increasingly wide market segment. However, to remain relevant and sustainable, Islamic banking must continue to develop products and services that meet the needs of diverse consumers. This research aims to explore the challenges and opportunities in developing sharia banking products to reach wider market segments, as well as their impact on financial inclusion and sustainable economic growth. Through a literature review and in-depth analysis, we identified key strategies in developing sharia banking products, including in-depth market research, product innovation, and cross-sector collaboration. We also evaluate the social, economic and regulatory implications of developing inclusive sharia banking products. Our findings highlight the importance of strengthening the innovation ecosystem and supporting a conducive regulatory framework to facilitate the sustainable growth of the Islamic banking industry. Thus, this research provides valuable insights for practitioners, academics and other stakeholders in understanding the dynamics of sharia banking product development in this ever-changing era.